Z Przewodnika po powieści Słowian Zachodnich (1945-1995) - Derlatka, Tomasz (Slavia Occidentalis, 2017)
This article contains a selection of notions from the Guidebook to the Novels of the West Slavs (a working title). The Guidebook is addressed predominantly  at researchers involved in comparative studies of the literatures of the West Slavs and it will cover fifty years (1945–1995) of novels written by West Slavic authors: Kashubian, Polish, Slovak (from Slovakia and the so-called  Lower Land), Czech as well as Upper and Lower Lusatian, and how they changed. Each entry will consist of a brief presentation of a novel’s content, bibliographical information (the subsequent editions, possible translations;  reception in the other languages will be limited exclusively to the West Slavs area), interpretation, a novel’s significance to a writer’s achievements,  specific national literature and, finally, the West Slavs’ novels as a whole, a selection (maximum five items) of the most important literature on the subject.